Comparison of human biopsy-derived and human iPS cell-derived intestinal organoids established from a single individual. (February 2023) - Inui, Tatsuya; Yamashita, Tomoki; Tomita, Junya; Yokota, Jumpei; Kishimoto, Wataru; Nakase, Hiroshi; Mizuguchi, Hiroyuki
Abstract: Rodent-derived intestinal tissues or human colon cancer-derived Caco-2 cells are widely used for in vitro pharmacokinetic tests. However, both entail problems such as species differences from humans and low expression levels of specific pharmacokinetic-related factors, respectively. To solve these problems, many groups, including ours, have been focusing on human biopsy-derived intestinal organoids (b-IOs) and human iPS cell-derived intestinal organoids (i-IOs). However, no reports directly compare the two. Therefore, we established both from a single individual and conducted a comparative study. b-IOs had a shorter doubling time than i-IOs: about 59 h vs 148 h. b-IOs also had higher gene expression levels of major drug transporters and drug-metabolizing enzymes than i-IOs. To evaluate their applicability to pharmacokinetics, both organoids were two-dimensionally cultured. Although the b-IO monolayer had a lower transepithelial electrical resistance than the i-IO monolayer, it had higher gene expression levels of many drug transporters and major drug-metabolizing enzymes than the i-IO monolayer. RNA-seq analysis showed that the i-IOs monolayer had a more complex structure than the b-IOs monolayer because the former contained neuronal and vascular endothelial cells. This study provides basic information for pharmacokinetic applications of human biopsy-derived and human iPS cell-derived intestinal organoids.